2010
DOI: 10.2138/am.2010.3557
|View full text |Cite
|
Sign up to set email alerts
|

AFM study of the epitaxial growth of brushite (CaHPO4{middle dot}2H2O) on gypsum cleavage surfaces

Abstract: The epitaxial overgrowth of brushite (CaHPO 4 ·2H 2 O) by the interaction of phosphate-bearing, slightly acidic, aqueous solutions with gypsum (CaSO 4 ·2H 2 O) was investigated in situ using atomic force microscopy (AFM). Brushite growth nuclei were not observed to form on the {010} gypsum cleavage surface, but instead formed in areas of high dissolution, laterally attached to gypsum [101] step edges. During the brushite overgrowth the structural relationships between brushite (Aa) and gypsum (A2/a) result in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 44 publications
3
23
0
Order By: Relevance
“…S3) confirmed that the microbial cells assembled primarily on the {011} planes of gypsum. It is likely that these specific planes have a rougher surface (23), which enables stronger adhesion, but may also facilitate accelerated water access (i.e., via enhanced dissolution kinetics) (24,25). Cyanobacteria-like cells were identified from morphological features in the microbial colonies ( Fig.…”
Section: Microorganisms Living In the Gypsum Rocksmentioning
confidence: 99%
“…S3) confirmed that the microbial cells assembled primarily on the {011} planes of gypsum. It is likely that these specific planes have a rougher surface (23), which enables stronger adhesion, but may also facilitate accelerated water access (i.e., via enhanced dissolution kinetics) (24,25). Cyanobacteria-like cells were identified from morphological features in the microbial colonies ( Fig.…”
Section: Microorganisms Living In the Gypsum Rocksmentioning
confidence: 99%
“…This 3D model investigates the influence of convection and the impact of the AFM tip/holder and general cell geometry on mass transport in a square ROI for a setup in which the bottom wall of the AFM fluid is formed by the crystal surface under investigation, as in a number of studies. 12,15,18,19,31,35,44,45 The surface concentration at the ROI is simulated at different flow rates and for different bulk concentrations. Dissolution of an ionic crystal is a stoichiometric reaction to satisfy the assumption of an electro-neutral solution and to maintain a constant charge at the crystal surface; as such, for illustrative purposes we reduce the mass transport model to the simulation of a single species.…”
Section: Theory and Modelingmentioning
confidence: 99%
“…2H 2 O was considered in depth by Heijnen and Hartman 18 , who presented a comparative study of their crystal morphologies using an A-setting for the three unit cells. More recent papers [19][20][21][22] illustrates how this structural similarity favors the development of oriented intergrowths between these three minerals.…”
Section: Introductionmentioning
confidence: 96%